The central auditory processing and continuous performance of children with Attention Deficit Hyperactivity Disorder (ADHD) in the medicated and non-medicated state - Alant, Erna (University of Pretoria, 2013)
Thesis (DPhil (Communication Pathology))--University of Pretoria, 2006.